2023
DOI: 10.1103/physreve.108.054901
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear effect of grain elongation on the flow rate in silo discharge

Agathe Bignon,
Mathieu Renouf,
Roland Sicard
et al.

Abstract: By means of two-dimensional numerical simulations based on contact dynamics, we present a systematic analysis of the joint effects of grain shape (i.e., grain elongation) and system size on silo discharge for increasing orifice sizes D. Grains are rounded-cap rectangles whose aspect ratio are varied from 1 (disks) to 7. In order to clearly isolate the effect of grain shape, the mass of the grains is keeping constant as well as the condition of the discharge by reintroducing the exiting grains at the top of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…CHAPTER 2. QUASI 2D MONO-LAYER SILO 2.10(a) and (b) suggests that the larger the aspect ratio of the particle, the smaller the discharge rate of the particles will be, which is consistent with the study of Bignon et al [64]. Although the analysis introduced by Janda et (2.12), with the parameters obtained from the fits to the vertical velocity and solid fraction profiles [Eqs.…”
Section: Discharge Ratesupporting
confidence: 74%
See 4 more Smart Citations
“…CHAPTER 2. QUASI 2D MONO-LAYER SILO 2.10(a) and (b) suggests that the larger the aspect ratio of the particle, the smaller the discharge rate of the particles will be, which is consistent with the study of Bignon et al [64]. Although the analysis introduced by Janda et (2.12), with the parameters obtained from the fits to the vertical velocity and solid fraction profiles [Eqs.…”
Section: Discharge Ratesupporting
confidence: 74%
“…Many studies have confirmed the scaling of both velocity and solid fraction profiles and its relationship with the discharge rate [22,[130][131][132][133]for spherical particles. Although this idea has also been tested for poly-disperse systems [152,153], only a recent numerical work validates its applicability to non-spherical particles performing the 2D numerical simulations of elongated particles having the same mass and same cross-sectional area [64]. In this paper, we present the results of a similar experiment done in the quasi 2D mono-layer silo setup for the spheres and two types of elliptical particles with different aspect ratios.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations